1983
DOI: 10.1002/1097-0142(19830101)51:1<57::aid-cncr2820510114>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium parvum versus BCG adjuvant immunotherapy in human malignant melanoma

Abstract: One‐hundred and sixteen patients with Stage I and Stage II malignant melanoma were randomized to treatment with either Bacillus Calmette‐Guerin (BCG) (Tice) or subcutaneous Corynebacterium parvum (Burroughs‐Wellcome). Life table analysis failed to reveal a difference between these two forms of treatment in 68 Stage I patients. The relapse rate was significantly reduced in Stage II patients trated with C. parvum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…The first systematic attempts at harnessing immunotherapy for melanoma involved microbial stimulants such as Bacillus Calmette–Guerin (BCG) . Although randomized trials did not demonstrate a benefit to BCG, subsequent analysis did demonstrate improved outcomes for patients who developed an immune response to therapy …”
Section: Part 2: Immunotherapymentioning
confidence: 99%
“…The first systematic attempts at harnessing immunotherapy for melanoma involved microbial stimulants such as Bacillus Calmette–Guerin (BCG) . Although randomized trials did not demonstrate a benefit to BCG, subsequent analysis did demonstrate improved outcomes for patients who developed an immune response to therapy …”
Section: Part 2: Immunotherapymentioning
confidence: 99%
“…Timing of vaccination in childhood may be critical, prior to imprinting of the immune system, given the lack of therapeutic benefit of BCG and vaccinia vaccination for treatment of melanoma patients later in life [21,22]. Based on the EORTC study, reintroduction of widespread neonatal BCG vaccination is an after surgery [34][35][36][37]. C. parvum never found widespread adoption as a therapeutic agent in melanoma or any other malignancy.…”
Section: A) Bcg and C Parvummentioning
confidence: 99%
“…Studies of C. parvum versus observation [74] and placebo [75] have failed to demonstrate any benefit. When compared with BCG therapy, however, two studies, [76,77] have shown C. parvum therapy to confer a statistically significant survival advantage, although these studies did not have a placebo arm. Although a benefit of BCG and C. parvum single-agent therapy over and above observation alone has not been definitively demonstrated, BCG continues to play a significant role as a control arm, as well as an immune adjuvant in combination with vaccine therapy in ongoing clinical trials.…”
Section: Immunostimulantsmentioning
confidence: 99%